Prospective Comparison of a Metal-Free Ceramic Total Knee Arthroplasty with an Identical Metal System - Trieb, Klemens; Ullmann, David; Metzinger, Katharina; Kramar, Reinhard; Mauerer, Andreas; Hofstätter, Stefan; Fiala, Rainer (Zeitschrift für Orthopädie und Unfallchirurgie, 2018)
Aims The aim of this open-label, prospective, short-term study was to carry out an initial comparison of a completely metal-free ceramic with a geometrically identical metallic arthroplasty over a 1-year follow-up period.Methods This study investigates a completely metal-free system using a composite matrix material containing aluminum oxide (Al2O3, BPK-S Integration, Peter Brehm GmbH, Weisendorf, Germany) or zirconium oxide (ZrO2, BPK-S Integration Ceramic, Biolox Delta-CeramTec GmbH, Plochingen, Germany). Eighty patients (40 in each group) received either a completely metal-free ceramic system (matrix of aluminum and zirconium oxide) or an anatomically identical metallic knee system made of a cobalt-chromium alloy. Clinical assessment was performed preoperatively, and during follow-up at 3 and 12 months, using the Knee Society Score, Oxford Knee Score, and EQ-5D-VAS. For radiological evaluation, standard preoperative and postoperative standardized radiographs were taken at the given follow-up visits.Results The postoperative clinical scores improved significantly at the 3- and 12-month follow-ups, but did not differ statistically between the two groups. The radiologically evaluated mean postoperative mechanical and anatomical axes showed proper alignment within both groups at all times. No revision surgery had to be performed, and no complications or loosening were recorded whatsoever.Conclusions To our knowledge, this is the first study comparing a total ceramic metal-free knee system with a geometrically identical metallic TKA (total knee arthroplasty). Longer follow-ups will be required to demonstrate the overall efficiency of this TKR and perhaps to expand its medical indication.
Keywords: knee; arthroplasty; ceramic